Författare—samhälle—media: En mediekritisk betraktelse av medietäckning om Knut-Hamsun-jubileet 2009 - Langhof, Julia (Nordlit, 2016)
The Knut Hamsun Jubilee 2009 was heavily criticized by nationals and internationals alike, which was reflected in a large number of media debates. The article critically analyzes the media coverage of the Knut Hamsun Jubilee 2009. It shows how the media’s coverage and rhetoric of the Jubilee effected the discussion about its legitimacy. Assuming that the media has an impact on the public’s negotiation of thought patterns, and that the media is capable of influencing public opinion, the article examines the following two aspects: What kind of persuasive strategies were used in public discussions in the press about the Knut Hamsun Jubilee 2009? How did the Norwegian Online Press deal with critical comments especially from foreign critics? The article aims at elaborating the media’s role in present public discussions about Writers and Literature.